2012
DOI: 10.1590/s0066-782x2012005000050
|View full text |Cite
|
Sign up to set email alerts
|

Valor prognóstico do peptídeo natriurético tipo B na mortalidade de pacientes com Síndrome Coronariana Aguda

Abstract: Background: The prognostic value of BNP in acute coronary syndrome (ACS) has been repeatedly assessed, but not completely well established. Literature data for establishing the best time for assessing BNP, be it on hospital admission or after coronary intervention, are controversial.Objective: To analyze BNP in non-ST segment elevation ACS (NSTE-ACS) in the long term, and to assess the association between BNP (pg/ml), death, coronary anatomy, and TIMI Risk Score.Methods: Forty patients with NSTE-ACS and tropon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
3
0
3
Order By: Relevance
“…However, the prognostic value of BNP in ACS has not been well established, although it has been repeatedly assessed. According to current understanding, baseline BNP measurement in ACS patients is an important risk stratification tool [47]; the findings of our study support this notion.…”
Section: Discussionsupporting
confidence: 83%
“…However, the prognostic value of BNP in ACS has not been well established, although it has been repeatedly assessed. According to current understanding, baseline BNP measurement in ACS patients is an important risk stratification tool [47]; the findings of our study support this notion.…”
Section: Discussionsupporting
confidence: 83%
“…The previous investigation confirmed the diagnostic and prognostic importance of BNP in patients with HF (26). However, a recent study showed the significant association of BNP with higher longterm mortality risk in patients diagnosed with ACS (27). In ACS patients, levels of BNP are likely increasing due to stiffening of left ventricular as a result of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 70%
“…No entanto, outros estudos usaram ou encontraram valores mais altos de BNP para demonstrar relação com prognóstico em SCA. Scotti et al 8 acompanharam 40 pacientes com SCA sem supradesnível de ST e troponina positiva e mensuraram o BNP na chegada e após 96 horas da admissão. Usando um cutoff de 300 pg/mL, os autores mostraram que o BNP foi forte preditor de mortalidade em quatro anos de seguimento com área sob a curva de 0,92.…”
Section: Discussionunclassified
“…Usando um cutoff de 300 pg/mL, os autores mostraram que o BNP foi forte preditor de mortalidade em quatro anos de seguimento com área sob a curva de 0,92. Além disso, demonstrou-se um risco relativo de morte 7,4 vezes maior naqueles com BNP acima de 300 pg/mL (p < 0,01) 8 .…”
Section: Discussionunclassified
See 1 more Smart Citation